Sharia Cooperative Readiness for Adopting the Industry 4.0: Evidence of Sharia Cooperatives in Bandung - Karnawati, Hennidah; Purwihartuti, Koernia; Kristianingsih, Kristianingsih; Setyowati, Tri (Jurusan Akuntansi Politeknik Negeri Bandung, 2024)
The phenomenon is a challenge to examine more deeply about how ready cooperatives in Indonesia, including Sharia cooperatives, face Industry 4.0, which is rolling rapidly following technological developments. The objectives of this research are knowing the existing conditions of internal and external factors of Islamic cooperatives in Bandung, for implementing industry 4.0 and .The method used in this research is descriptive. This research was conducted with a cross sectional one shoot. The sampling technique used is total sampling. Qualitative data collection techniques through deep online interviews to a sharia cooperative management in Bandung. Quantitative data were collected using a questionnaire method of about 7 of sharia cooperative in Bandung. The result of this research is the analysis of the internal environmental scan obtained the strength of the Islamic cooperative in the form of key points for success, efficient sources and use of funds, employee competence, reward system, cooperative social responsibility. Meanwhile, the weakness is in the form of insufficient funds. The results of external environmental scanning analysis are in the form of service innovation, collaboration with system developers, collaboration with creditors, automation, vendor / supplier support, method support. The strategies that can be selected are in the form of market development, market penetration, product development, forward integration, backward integration, horizontal integration, related diversification.